Comparison of tramadol and lornoxicam in intravenous regional anesthesia: a randomized controlled trial - Çelik,Hande (2016)
BACKGROUND AND OBJECTIVES: Tourniquet pain is one of the major obstacles for intravenous regional anesthesia. We aimed to compare tramadol and lornoxicam used in intravenous regional anesthesia as regards their effects on the quality of anesthesia, tourniquet pain and postoperative pain as well. METHODS: After the ethics committee approval 51 patients of ASA physical status I-II aged 18-65 years were enrolled. The patients were divided into three groups. Group P (n = 17) received 3 mg/kg 0.5% prilocaine; group PT (n = 17) 3 mg/kg 0.5% prilocaine + 2 mL (100 mg) tramadol and group PL (n = 17) 3 mg/kg 0.5% prilocaine + 2 mL (8 mg) lornoxicam for intravenous regional anesthesia. Sensory and motor block onset and recovery times were noted, as well as tourniquet pains and postoperative analgesic consumptions. RESULTS: Sensory block onset times in the groups PT and PL were shorter, whereas the corresponding recovery times were longer than those in the group P. Motor block onset times in the groups PT and PL were shorter than that in the group P, whereas recovery time in the group PL was longer than those in the groups P and PT. Tourniquet pain onset time was shortest in the group P and longest in the group PL. There was no difference regarding tourniquet pain among the groups. Group PL displayed the lowest analgesic consumption postoperatively. CONCLUSION: Adding tramadol and lornoxicam to prilocaine for intravenous regional anesthesia produces favorable effects on sensory and motor blockade. Postoperative analgesic consumption can be decreased by adding tramadol and lornoxicam to prilocaine in intravenous regional anesthesia.